Post-merger management : value creation in M&A integration projects - Meynerts-Stiller, Kirsten; Rohloff, Christoph (Emerald Publishing Limited, 2019)
Companies acquire and merge to generate accelerated value growth. But merger integrations pose an enormous challenge to organisations: they are fraught with over-inflated expectations of making rapid synergy gains, laden with pitfalls inherent to complex organisational change, charged with emotion and are often influenced by socio-psychological dynamics. This complicated situation poses risks, and it is no surprise that many merger integrations turn out to be botched jobs.This book pools the current know-how, and closes important knowledge gaps, to offer hands-on advice and practical answers to the many 'how to' questions relating to merger implementation. It also explains the broader M&A context in which integration projects are rooted, providing a crucially important understanding of how to assess the chances of realising synergy potential and evaluate integration risks. The book demonstrates how integration can succeed and provides a candid overview of everything that needs to be done to navigate one of the most challenging areas of entrepreneurial activity. Business integration managers should view this as a vital instruction manual containing the essentials for the successful organisation of merger integration projects. The book guides PMI-managers through all the relevant fields of action to ensure a successful merger which forms a functioning and profitable business.